Estudo sobre o consumo de energia elétrica em aglomerados de computadores com utilização do framework OAR - Albiero, Fábio Weber (2013)
Our society increasingly relies on the use of computers to perform various tasks. The high rate of use of such equipment causes the increase in electricity consumption. To meet the growing demand for energy, there are two possible solutions. The first solution is to increase production, which is a difficult task because of the need to build new sources of energy. The second solution is to promote more efficient use of energy, so that the demand for computing power can be met without increasing the power consumption. That means optimizing the energy performance of electronic devices of the computational systems in this case. The systems of high performance (computer clusters and grids) are excellent targets for optimizing the energy consumption, since they consume large amount of electricity. Therefore, this paper presents a study on the energy consumption in computer clusters through the use of the OAR framework (Optimal Allocation of Resources). The study aims to measure the electricity consumed in various settings of computer clusters. In terms of computational resources available, the measurement will help to answer important questions concerning to the management of electrical energy, such as: what is the best setting to save energy and how much energy can be saved.